Does Internal Migration Lead to Faster Regional Convergence in Turkey? An Empirical Investigation - Murat Kırdar; Sirin Saracoglu (Turkish Economic Association, 2006)
In this study, we examine whether internal migration in the last 30 years in Turkey has had any effect on the speed of convergence across Turkish provinces. According to our results, contrary to the predictions of the standard neoclassical theory, for 1975-2000,internal migration is not conducive to faster convergence across provinces in Turkey. One probable reason is that marginal returns to capital in most net outmigration provinces and regions are relatively lower than those in the net in-migration provinces and regions in Turkey. Accordingly, the incentives to invest in capital in net-out migration regions may well be less than those in the net in-migration regions.Faced with lower investment in gross capital formation, and thus lower economic growth, net out-migration provinces and regions may not benefit from out-migration in terms of convergence in per capita income.
Keywords: 330